High Performance Computing - Zelkowitz, Marvin V., 1945- (Advances in computers, 2008)
This is volume 72 of Advances in Computers, a series that began back in 1960 and is the oldest continuing series chronicling the ever-changing landscape of information technology. Each year three volumes are produced, which present approximately 20 chapters that describe the latest technology in the use of computers today. In this volume 72, we present the current status in the development of a new generation of high-performance computers. The computer today has become ubiquitous with millions of machines being sold (and discarded) annually. Powerful machines are produced for only a few hundred U.S. dollars, and one of the problems faced by vendors of these machines is that, due to the continuing adherence to Moore's law, where the speed of such machines doubles about every 18 months, we typically have more than enough computer power for our needs for word processing, surfing the web, or playing video games. However, the same cannot be said for applications that require large powerful machines. Applications such as weather and climate prediction, fluid flow for designing new airplanes or automobiles, or nuclear plasma flow require as much computer power as we can provide, and even that is not enough. Today's machines operate at the teraflop level (trillions of floating point operations per second) and this book describes research into the petaflop region (1,015 FLOPS). The six chapters provide an overview of current activities that will provide for the introduction of these machines in the years 2011 through 2015.